Family and Creative Economy in Sunan Gunung Djati Religious Tourism Area, Cirebon, Indonesia - Muamar, Afif; Rijal, Syamsul; Faozi, Moh. Mabruri; Mahfudin, Mahfudin; Tohayudin, Tohayudin (El-Usrah: Jurnal Hukum Keluarga, 2024)
This study aims to determine efforts to create a harmonious family, to identify activities, and to determine the factors that influence the income level of creative economy actors. This study employed a qualitative approach to examine the role of families in the creative economy and minimize business weaknesses and factors that influence the income of around 350 service and business sectors. This study found that first, efforts to create a harmonious life for creative economy actors, namely creating household conditions that are communicative and warm, as well as instilling an attitude of acceptance and instilling a sense of trust in married couples. Second, tourism is a labor-intensive sector that includes services and the business world. Third, the main factors that influence the level of creative economy income are internal and external factors. This research provides new insights into a comprehensive review of the family and creative economy of religious tourism at the Sunan Gunung Djati Cemetery, Cirebon.